2016
DOI: 10.1016/j.jstrokecerebrovasdis.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I and Paraoxonase-1 Are Potential Blood Biomarkers for Ischemic Stroke Diagnosis

Abstract: Background Blood biomarkers for ischemic and hemorrhagic stroke diagnosis remain elusive. Recent investigations suggested that apolipoprotein (Apo), matrix metalloproteinase (MMP), and paraoxonase-1 may be associated with stroke. We hypothesized that Apo A-I, Apo C-I, Apo C-III, MMP-3, MMP-9, and paraoxonase-1 are differentially expressed in ischemic stroke, hemorrhagic stroke, and controls. Methods In a single-center prospective observational study, consecutive stroke cases were enrolled if blood samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Figure gives the schematic representation of the systematic review. After scanning through the title and abstract of each article, 37 full text studies were assessed for eligibility; out of which 18 articles from 2004 to 2017 were found relevant and were included in our systematic review. The review highlights the role of 10 single biomarkers (ApoC‐1, ApoC‐III, GFAP, RBP4, hs‐CRP, APC‐PCI, Apo‐AI, Paraoxonase‐1, BNP, S100B) and seven panels consisting of several different biomarkers for distinguishing the two stroke types.…”
Section: Resultsmentioning
confidence: 99%
“…Figure gives the schematic representation of the systematic review. After scanning through the title and abstract of each article, 37 full text studies were assessed for eligibility; out of which 18 articles from 2004 to 2017 were found relevant and were included in our systematic review. The review highlights the role of 10 single biomarkers (ApoC‐1, ApoC‐III, GFAP, RBP4, hs‐CRP, APC‐PCI, Apo‐AI, Paraoxonase‐1, BNP, S100B) and seven panels consisting of several different biomarkers for distinguishing the two stroke types.…”
Section: Resultsmentioning
confidence: 99%
“…A novel quantitative proteomic technology, isobaric tagging for relative and absolute quantitation (iTRAQ), has recently become a powerful tool to characterize differentially expressed proteins and identify the biomarkers for central nervous systems disorders, particularly for stroke [35]. The new technology allows broad protein biomarker screenings, offering the hope to better understand the pathophysiological mechanisms underlying AIS due to LVO.…”
Section: Introductionmentioning
confidence: 99%
“…79 This conclusion is supported by a clinical study where ApoA-I levels were lower in ischemic stroke cases vs controls. 80 ApoB, which constitutes the gross majority of Apos found in LDL, is considered atheroprone, as reported in a meta-analysis, 79 although no significant correlation with major cardiovascular events was found in a large cohort study. 81 The existence of two allele proteins (ApoB100 and ApoB48), might bias these findings, and no report of specific determination of ApoB100 related to carotid atherosclerosis has been published as yet.…”
Section: Biomarker Descriptionsmentioning
confidence: 98%